High Hydrostatic Pressure Inducible Trimethylamine N-Oxide Reductase Improves the Pressure Tolerance of Piezosensitive Bacteria Vibrio fluvialis - Yin, Qun-Jian; Zhang, Wei-Jia; Qi, Xiao-Qing; Zhang, Sheng-Da; Jiang, Ting; Li, Xue-Gong; Chen, Ying; Santini, Claire-Lise; Zhou, Hao; Chou, I-Ming; Wu, Long-Fei (Frontiers in Microbiology, 2018)
High hydrostatic pressure (HHP) exerts severe effects on cellular processes including impaired cell division, abolished motility and affected enzymatic activities. Transcriptomic and proteomic analyses showed that bacteria switch the expression of genes involved in multiple energy metabolism pathways to cope with HHP. We sought evidence of a changing bacterial metabolism by supplying appropriate substrates that might have beneficial effects on the bacterial lifestyle at elevated pressure. We isolated a piezosensitive marine bacterium Vibrio fluvialis strain QY27 from the South China Sea. When trimethylamine N-oxide (TMAO) was used as an electron acceptor for energy metabolism, QY27 exhibited a piezophilic-like phenotype with an optimal growth at 30 MPa. Raman spectrometry and biochemistry analyses revealed that both the efficiency of the TMAO metabolism and the activity of the TMAO reductase increased under high pressure conditions. Among the two genes coding for TMAO reductase catalytic subunits, the expression level and enzymatic activity of TorA was up-regulated by elevated pressure. Furthermore, a genetic interference assay with the CRISPR-dCas9 system demonstrated that TorA is essential for underpinning the improved pressure tolerance of QY27. We extended the study to Vibrio fluvialis type strain ATCC33809 and observed that the same phenotype of TMAO-metabolism improved the pressure tolerance. These results provide compelling evidence for the determinant role of metabolism in the adaption of bacteria to the deep-sea ecosystems with HHP.